NATO's Nuclear Sharing Arrangements Revisited in Light of the NPT and the TPNW. (25th September 2021) - Hayashi, Mika
Abstract: The nuclear sharing arrangements of the North Atlantic Treaty Organization (NATO) are arrangements that pre-date the Nuclear Non-Proliferation Treaty (NPT). This article revisits the nuclear sharing arrangements in light of the NPT, then examines the issues in light of a new treaty, the Treaty on the Prohibition of Nuclear Weapons (TPNW). The question of the compatibility between these arrangements and the NPT was initially solved by an understanding that the stationing of the US nuclear weapons in host States did not involve transfer of ownership or transfer of control of these weapons to host States. Compared to the initial acceptance of this interpretation, the contemporary acceptance is less solid. The nuclear sharing arrangements are questioned or criticised in the NPT Review process, both by non-nuclear-weapon States and nuclear-weapon States. In contrast, with regard to the TPNW, there seems to be no controversy; the TPNW explicitly provides that the States Parties must not allow stationing of nuclear weapons. The nuclear sharing arrangements would be incompatible with this prohibition. The article also briefly deals with a separate question, whether a client State of extended nuclear deterrence that does not allow stationing of nuclear weapons in its territory would also contravene the prohibitions in the TPNW. Given the scope and the nature of provisions of the TPNW, the article concludes that it would, if such a client State joins the treaty without a change in its policy regarding extended deterrence.